Growth, Equity and Environmental Aspects of Agricultural Development in Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishThe challenge of sustaining agricultural development consists of three complementary and synergies dimensions, i.e. maintaining economic growth, promoting equity and protecting the environment. Price support policy is essential for enhancing technological adoption, increasing output and farmer income. In addition, dynamic institutional and vision of agricultural development, efficiency improvement and technological generation played an important role in the production strategy. Off-Java wetland rice farmers have greater opportunities to gain production through enhanced technical or economic efficiency by improving their managerial skills. In contrast, for dry land rice and secondary crops' farmers, only research and technological breakthrough can solve the low productivity problems and increase farmers' income. Poverty alleviation requires comprehensive efforts that should be conducted in a simultaneous manner. However, the monetary and economic crisis recently faced by the government, provides strong reasons to focus attention on agriculture and rural development availing the best chance to stimulate sustainable growth that address food security, poverty and income distribution concerns. The government has implemented some programs dealing with sustainable agricultural development. Some of those programs were successfully implemented such as integrated pest management (IPM) and Brantas watershed resource management. On the other hand, soil conservation technologies such as alley cropping and timber-food crops farming system (TFS) have difficulties for wider implementation. To promote the implementation of those technologies, the farmer have to be facilitated with better economic environment and land ownership rights for legal certainty on cultivated land. IndonesianTantangan pembangunan pertanian berkelanjutan mencakup tiga faktor yang bersifat sinergis dan komplementer yaitu mempertahankan laju pertumbuhan, pengurangan kemiskinan dan mencegah kerusakan lingkungan. Kebijaksanaan harga yang diterapkan selama ini dinilai telah berhasil mendorong adopsi teknologi, peningkatan produksi, dan pendapatan petani. Disamping itu pengembangan kelembagaan dan visi pembangunan pertanian secara dinamis, peningkatan efisiensi dan penciptaan teknologi baru telah memainkan peranan penting dalam strategi peningkatan produksi. Bagi petani padi sawah khususnya di luar Jawa masih terbuka peluang cukup besar untuk mendapatkan tambahan produksi melalui perbaikan efisiensi usahatani dengan memperbaiki kemampuan manajemen petani. Bagi petani lahan kering dan palawija, hanya penelitian dan terobosan teknologi baru yang dapat memecahkan masalah peningkatan produksi dan pendapatan petani. Upaya pengentasan kemiskinan membutuhkan program yang komprehensif dan perlu dilaksanakan secara simultan. Namun dalam situasi krisis moneter dan mampu mempertahankan keberlanjutan pembangunan dengan sasaran utama peningkatan ketahanan pangan, pengurangan kemiskinan, dan perbaikan distribusi pendapatan. Pemerintah telah menerapkan beberapa program yang berkaitan dengan proteksi sumberdaya alam dan lingkungan> Beberapa program telah berhasil dilaksanakan secara memadai seperti pemberantasan hama terpadu (PHT) dan pengelolaan daerah aliran sungai seperti Daerah Aliran Sungai (DAS) Brantas. Di lain pihak program konservasi tanah dan air seperti teknologi tanaman lorong dan sistem usahatani tumpang sari tanaman keras dan komoditas pangan menghadapi tantangan dalam pengembangannya. Dalam mendorong implementasinya di lapangan petani perlu difasilitasi dengan kredit, ketersediaan sarana produksi, penyuluhan dan pembinaan, serta kepastian hukum dalam penguasaan lahan.